Strategy Development for Public Services to Promote People’s Life Quality in Subdistrict Administrative Organization in Kamphaengphet - Adulyathorn, Weeradej; Chutun, Noppakhun; Juninn, Pensri (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2022)
The research of Strategy Development for Public Services to Promote People’s Life Quality in Subdistrict Administrative Organization in Kamphaengphet have objectives 1) To Studied about circumstances, problem and The factor that about Public service to promote people’s life quality 2) to prepared the strategy development for Public service to promote people’s life quality and 3) to evaluation the strategy development for Public service to promote people’s life quality. The sample group in this research were 136 director of Subdistrict Administrative Organization, 314 employees of Subdistrict Administrative Organization and 348 people aged 18 years old over, 117 people Development and assessment contributors by using questionnaire, Interviews, Workshop, Seminar Reference Experts and using assessment form. The results revealed that 1) the circumstances, problem and the factor that about Public service to promote people’s life quality. The Condition found that some of the employees Subdistrict Administrative Organization are willing and they have good attitude toward the service and they have good abilities and knowledge on their duty and their work for each job position. The director has knowledge and abilities about the integrated management and emphasize with promote people’s life quality. They gave opportunity to every department participated with development problem and they found that the budget isn’t enough for operation and the government has delay allocation and the limit of using the budget are affected to growth engine plan that it was unexpected, which is the high-level problem. The strength factor found that the director and employee have knowledge and abilities for their work as integrated, good attitude. The weak factor found that the employee isn’t enough for position and too many transferences, the budget isn’t enough. The irrelevant factor found that the statute, law, rules, government policy are reinforcement to Subdistrict Administrative Organization for easier to work. The obstacle factor found that the area size has affected with different way to the quality of occupation and The Subdistrict Administrative Organization community. 2) The strategy of Development for public Services to promote People’s Life quality included Vision, Mission, and Goals. The purpose of strategy, Indicators and Measures and the development strategy has 8 strategy includes 1) to promote the management plan procedure by integrated with Local development plan in every level. 2) Develop plans and implement them effectively 3) follow up Management plans provided the public services to promote people’s life quality to meet the standards 4) developed the data system for increased the limit of access ability to the public services to promote people’s life quality 5) to develop and using the clean innovative for public service 6) to reinforce and develop the volunteer community for supporting in every parts of public service people’s quality life 7) to enhanced integrated management plan and the process of the public service to promote people’s life quality under cooperation of all department 8) to improve the system and mechanism directing, follow up, evaluation and the performance report of public service to promote people’s life quality that accord with the good governance concrete. 3) The assessment report of Strategy Development for Public Services to Promote People’s Life Quality found that the result of consistency is suitable and high level of satisfaction.